IoT-based Tetra Health Surveillance System (THSS) (International Journal of Scientific Research and Management (IJSRM), 2021)
Nowadays, we are very conscious about our health because of how the covid-19 virus has changed our day-to-day life. IoT healthcare devices can be really helpful in this pandemic situation when we are all stuck in our homes. We have witnessed that IoT devices got very popular during this pandemic and the term ‘IoT’ also got really famous in the healthcare industry. If the hospital is far away from someone’s home, then using these portable monitoring devices one can keep track of their well-being. Health is the most important aspect for any individual, so in this paper, we propose a solution named the IoT-based Tetra Health Surveillance System (THSS) which helps us to monitor people who live by themselves or elderly people who want to continuously monitor their vitals due to underlying health conditions. Our proposed solution also displays the Temperature and Humidity, Blood pressure, Body Temperature, and SpO2/Blood Oxygen level at any given moment. This work will have a significant technical and commercial benefit because an individual can monitor all their vitals in one place and they don’t have to buy separate pieces of equipment to monitor each one of their vitals. This proposed device can be an all-in-one solution that is cost-effective and easy to use.